QUALITY AND ANTIOXIDANT ACTIVITY TEST OF ALBEDO WATERMELON (Citrullus lanatus Tunb.) COMBINATION GUAVA FRUIT COMBINATION (Psidium guajava L.) - Rusita, Youstiana Dwi; Nasikin, M. Ali; Agustin, Arum Dwi (Jurnal Jamu Kusuma, 2024)
Jam is a food product with a gel or semi-solid consistency that is spread on food made from processed fruits and sugar without the addition of other food ingredients and permitted food additives. This study created a formulation of jam preparations from the albedo of watermelon rind (Citrullus lanatus Tunb.) in combination with guava fruit (Psidium guajava L.) because they contain vitamin C, which has antioxidant activity. The purpose of this study was to determine the formulation and antioxidant activity of the albedo jam preparation of watermelon rind (Citrullus lanatus Tunb.) and guava fruit (Psidium guajava L.). This study used a quantitative descriptive method with observations of jam quality according to SNI 01-3746-2008. The test parameters were jam quality tests, including organoleptic, pH, water content, colour test, and antioxidant activity tests. The organoleptic results of the jam had a bright red colour with a distinctive aroma of watermelon and red guava and had a slightly sour, sweet taste. The results of the pH test of the jam on F1, F2, and F3 were respectively 3.72 ± 0.025, 3.84 ± 0.017, and 3.85 ± 0.032. The results of the water content test of the jam on F1, F2, and F3 were respectively 29.34 ± 0.464, 29.18 ± 0.375, and 28.71 ± 0.437. The results of the jam colour test showed positive vitamin C content. The IC50 values of the jam preparations on F1, F2 and F3 were respectively 155.345 ppm, 145.581 ppm, and 130.241 ppm. The F1 jam preparation is a weak antioxidant, while F2 and F3 are moderate antioxidants.